(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Hypertension is a non-communicable disease that has an increasing prevalence every year. The quality of the variety of food consumption affects the incidence of hypertension. The purpose of this study was to describe the dietary diversity, food preferences, and systolic blood pressure in hypertensive patients. This study used a survey method with a cross sectional approach with 40 research subjects using a simple random sampling method. Data collection includes measurement of systolic blood pressure, Dietary Diversity Score (DDS), and food preferences. The results showed that most of the subjects included in the category of uncontrolled hypertension (92.5%) and had a moderate quality of dietary diversity (52.5%). This is supported by the subject's food preferences including starchy staple foods, vegetables, fruit, meat, fish, and nuts. It can be concluded that the quality of the dietary diversity in hypertensive patients is still lacking with similar food preferences between favorite foods and foods that are often consumed. The government or local authorities need to educate the public to consume a variety of foods to support health status.